Skagway street scene, summer of 1897. - Curtis, Asahel, 1874-1941 (1897)
Clancy's Saloon on right, operated by Frank and John Clancy. Klondike Gold Rush. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number